2006
DOI: 10.1002/syn.20318
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal caffeine administration causes a permanent increase in the dendritic length of prefrontal cortical neurons of rats

Abstract: We studied the morphological changes of the dendritic length of the pyramidal neurons of the prefrontal cortex (PFC) induced by the effect of chronic administration of caffeine in the neonatal rat. The caffeine (50 mg/kg, s.c.) was injected from day 1 after birth (P1) to day 12 (P12). The morphology of the pyramidal neurons of layer 3 of the PFC was investigated in these animals at two different ages, before puberty (P35) and after puberty (P70). Before the animals were sacrificed by using overdoses of sodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 53 publications
2
26
2
Order By: Relevance
“…Importantly also, caffeine actions do not result solely from A 2A R antagonism since caffeine is an antagonist of different adenosine receptor subtypes. However, several studies have indeed shown that gestational exposure to caffeine may alter the normal development of the brain with cognitive consequences to the adult brain (Juárez-Méndez et al 2006;Soellner et al 2009;Silva et al 2013;Mioranzza et al 2014), by delaying migration and insertion of GABAergic neurons into the hippocampal circuitry (Silva et al 2013), by decreasing either BDNF or TrkB receptor levels (Mioranzza et al 2014), by affecting the different adenosine receptors expression during neural Fig. 11 Adenosine A 2A Rs activation increases microtubule dynamics.…”
Section: Adenosine a 2a Receptor Activation Increases Microtubule Dynmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly also, caffeine actions do not result solely from A 2A R antagonism since caffeine is an antagonist of different adenosine receptor subtypes. However, several studies have indeed shown that gestational exposure to caffeine may alter the normal development of the brain with cognitive consequences to the adult brain (Juárez-Méndez et al 2006;Soellner et al 2009;Silva et al 2013;Mioranzza et al 2014), by delaying migration and insertion of GABAergic neurons into the hippocampal circuitry (Silva et al 2013), by decreasing either BDNF or TrkB receptor levels (Mioranzza et al 2014), by affecting the different adenosine receptors expression during neural Fig. 11 Adenosine A 2A Rs activation increases microtubule dynamics.…”
Section: Adenosine a 2a Receptor Activation Increases Microtubule Dynmentioning
confidence: 99%
“…Data are expressed as mean ± -SEM from 200 microtubule plus ends, counted from at least ten neurons per condition per culture, taken from two independent cultures, where all conditions were tested in each culture. Statistical significance was assessed by one-way ANOVA followed by Bonferroni correction for multiple comparisons (b) and by an unpaired Student's t test for comparison with control (bar on the left) (d): *p \ 0.05; ns (not statistically significant), as compared with control (first bar on the left, absence of any drug) or as indicated by the horizontal bars over the columns Brain Struct Funct development (Soellner et al 2009), or by modifying the dendritic morphology of pyramidal neurons of the rat prefrontal cortex (Juárez-Méndez et al 2006). Further studies are required to appraise whether moderate exposure to caffeine at early developmental stages affects axonal elongation and its impact upon neuronal network structure and function.…”
Section: Adenosine a 2a Receptor Activation Increases Microtubule Dynmentioning
confidence: 99%
“…However, little is known regarding the effects of higher doses of caffeine on the immature brain, in particular its effects on the development of white matter (WM), a brain component that is very vulnerable to injury in preterm infants (7,8). Although several studies have assessed the effects of high-dose caffeine on the developing brain, these studies show both beneficial (9,10) and detrimental (11,12) effects. The majority of previous studies have been conducted in rats and mice (9)(10)(11)(12), species in which white to gray matter (GM) ratio is not comparable to humans and in which brain development occurs predominantly postnatally.…”
mentioning
confidence: 99%
“…Although several studies have assessed the effects of high-dose caffeine on the developing brain, these studies show both beneficial (9,10) and detrimental (11,12) effects. The majority of previous studies have been conducted in rats and mice (9)(10)(11)(12), species in which white to gray matter (GM) ratio is not comparable to humans and in which brain development occurs predominantly postnatally. Furthermore, previous studies have used widely differing dosing regimens.…”
mentioning
confidence: 99%
“…Some animal studies have reported negative effects related to caffeine, including disruption of sleep, spatial learning and growth,3 transient inhibition of astrocytogenesis4 and increased neuronal dendritic length 5. One of the most worrying traits as regards neonatal medicine is the potential for vasoconstriction, especially in the brain and gut 6.…”
Section: Commentarymentioning
confidence: 99%